PENERAPAN REKRUTMEN DAN PELATIHAN GURU SEKOLAH MINGGU DI GBI METRO PERMATA - Yohanes Siagian; Andreas Eko Nugroho (STT Bethel The Way, 2019)
This study aims to examine the importance of the recruitment of human resources (HR) who are part of the servants at GBI Metro Permata and provide constructive input to Sunday School services through the availability of servants, training methods and continuity of the service of S.M. at GBI Metro Permata. This study uses the method of Library Studies and Qualitative Research Methods Descriptive Analysis. Data analysis in qualitative research uses inductive data analysis. Data collected in the form of interviews and field notes. In the study of the biblical text using Biblical Studies. Biblical Studies uses the discussion of biblical texts with exposition principles or methods. From the results of this study it was found that the recruitment process carried out must pay attention to the qualifications set by the church. Finally the church could find the teacher of S.M. competent and qualified. Service activities carried out by teachers of S.M. can run effectively and systematically, so that the teachers obtained S.M. who are competent and committed to doing their services. In conclusion, the theories regarding recruitment must have a role, goals, resources, qualifications and processes for recruiting. It is important for an organization, especially a church, to have a training program for each field or categorical ministry. Theories about teacher S.M. which has been stated by experts that the history of the establishment of S.M. began in the 18th century, to become a teacher of S.M. must also have terms and conditions for age. In order to get the teachers of S.M. who are competent and committed to their service.